Arabic Linguist Perspective on Ibn Jinni's Ideas About Derivation: Comparative Study of Al-Suyūṭī and Emīl Badī’ Thought - Nahdliyyatul Azimah (Alsuna: Journal of Arabic and English Language, 2020)
Purpose - This research aims to illustrate the views of Al-Suyūṭī and Emīl Badī’ Ya’qūb about the thought of derivation according to Ibn Jinnī, as well as the location of the similarities and differences between their thoughts. Design/methodology/approach - This research study relies solely on literary studies or documentation of manuscripts, especially the works of Ibn Jinny, Al-Suyūṭī, and Emīl Badi' Ya’qūb. Findings - The result of this study that three linguists (Ibn Jinnī, Al-Suyūṭī, and EmīlBadi' Ya’qūb) agreed to challenge the definition of derivation. Al-Suyūṭī agreed to the thought of Ibn Jinnī in the division of derivation. As for Emīl, different opinions with the thought of Ibn Jinnī in three things, namely: Ibdāl, Naḥt (acronym), and the division of derivation. On the other side of Al-Suyūṭī denied the idea of Ibn Jinny in two respects, namely: derivation and naming of al-Ishtiqāq al- Akbar. Originality/value - Learners of Arabic language and religious studies students must study derivation science and are not confined to grammar and exclusivity. Because derivation science is an art that distinguishes the Arabic language from all other languages. Paper type - Conceptual Paper